Computer animation for hearing impaired application - Ng, Hon Wai. (2011)
This report documents the student’s 2 Semesters research and development of the Final Year Project (FYP) named Computer animation for hearing impaired application from year 2010/201l, under the supervision of Project supervisor Associate Professor Chau Lap Pui.